Estrategias de talento humano para la cooperativa CACPE Pastaza agencia mariscal de la ciudad de Puyo y el síndrome de Burnout - Gallardo Valdiviezo, Grace Estefanny (2025)
The present investigation project had the goal to design human talent strategies to alleviate burnout syndrome in the CACPE Pastaza Cooperative employees, at the Mariscal Agency, in the city of Puyo. The problem came about due to the growing workload at the Cooperative in recent years and the lack of adequate strategies to deal with it, which has generated high levels of stress, depersonalization and low personal fulfillment. These elements coincide with the presentation of the Burnout phenomenon and that have been affecting performance and well-being. Furthermore, the investigation was conducted with a mixed methodology, combining quantitative and qualitative focuses. Surveys based on the Maslach Burnout Inventory (MBI) were given to the employees and the head of the agency was interviewed. In addition, inductive-deductive, analytic-synthetic and descriptive-systematic methods were utilized to analyze the information and better understand the reach of the problem, as evidenced in the results which show that 74.6% of employees show a high level of emotional exhaustion, 76.19% show signs of depersonalization and 60.32% have low personal fulfillment. Finally, in order to take on this challenge, human resource strategies focused on improving the organization’s environment, internal communication and stress management are proposed, such as how to encourage professional development, including programs for well-being, teambuilding, appreciation and training, with the end goal of fighting against the factors that contribute to burnout development, and instead of this, strengthen motivation and optimize operative efficiency within the cooperative.